Supplementary feeding of roe deer (Capreolus capreolus L) with late harvested hay. A pilot study - Rehbinder, C.; Ciszuk, P. (Rangifer, 1985)
In order to increase the fodder available for roedeer during wintertime, late harvested hay was placed on racks early in November in three consecutive years. Freeezing kept the hay dry and fresh during all three winters. In the first winter, with much snow, the bulk of the hay was consumed whereas consumption in the two subsequent mild winters was low and selective. The crude protein content of the hay was low (3.5 - 8.4% dry matter). Metabolizable energy estimated from digestion in vitro was 3.5 — 5.6 MJ per kg dry matter. Rumen liquor from roe deer during a mild winter gave lower in vitro digestion than liquor from sheep fed with ordinary rations. The value of this poor hay for roe deer is discussed with respect to the animals requirements, seasonal adaption, the energy and protein content of the hay, water consumption and normal behavior. The results indicate that late harvested hay may be more suitable than regularly harvested hay or concentrates to help roe deer to survive spells of severe winter conditions. With late harvested hay placed out at several localized feeding sites, the risks of indigestion and dehydration, associated with a more concentrated, feed, are minimized and the ranking among the roe deer in particular will be less important and thus more animals will have improved prospects of gaining access to the fodder.Tilskottsutfodring av rådjur (Capreolus capreolus L) med sent skordat ho. En pilotstudie.Abstract in Swedish / Sammanfattning: I avsikt att, for rådjur, oka mångden tillgångligt foder under vintertid, skordades och håssjades ho i borjan av november under tre på varandra foljande år. Hoet fros torn och holl sig fårskt alla vintrarna. Forstå vintern med mycket sno konsumerades huvuddelen av hoet medan de två foljande milda vintrarna konsumptionen var låg och selektiv. Mångden råprotein i hoet var lågt (3.5 — 8.4 % i torrsubstans). Innehållet av omsåttbar energi beråknad från digestion in vitro var 3.5 — 5.6 MJ per kg torrsubstans. Våmvåtska från rådjur under en mild vinter gav lagra in vitro digestion ån våmvåtska från ordinårt utfodrade får. Vårdet av det mycket sent skordade hoet for rådjur diskuteras med utgångspunkt från djurens behov, såsongmåssiga adaption, energi- och proteininnehåll i hoet, vattenkonsumtion och normala beteende. Resultatén pekar på att, sent skordat ho kan vara låmpligare ån på normal tid skordat ho eller kraftfoder att hjålpa rådjur att overleva perioder med svåra vinterforhållanden. Med sent skordat och håssjat ho, vilket gjorts tillgångligt på ett flertal utfodringsplatser, minskar riskerna for våmindigestion och dehydrering, forenade med en mer hogvårdig utfodring, samtidigt som djurens inbordes rangordning blir mindre betydelsefull. Det senare innebarande att fler djur får tillgång till fodret.